Factors Affecting Daily Cochlear Implant Use in Children: Datalogging Evidence. - Easwar, Vijayalakshmi; Sanfilippo, Joseph; Papsin, Blake; Gordon, Karen (Journal of the American Academy of Audiology)
Background: Children with profound hearing loss can gain access to sound through cochlear implants (CIs), but these devices must be worn consistently to promote auditory development. Although subjective parent reports have identified several factors limiting long-term CI use in children, it is also important to understand the day-to-day issues which may preclude consistent device use. In the present study, objective measures gathered through datalogging software were used to quantify the following in children: (1) number of hours of CI use per day, (2) practical concerns including repeated disconnections between the external transmission coil and the internal device (termed "coil-offs"), and (3) listening environments experienced during daily use. Purpose: This study aimed to (1) objectively measure daily CI use and factors influencing consistent device use in children using one or two CIs and (2) evaluate the intensity levels and types of listening environments children are exposed to during daily CI use. Research Design: Retrospective analysis. Study Sample: Measures of daily CI use were obtained from 146 pediatric users of Cochlear Nucleus 6 speech processors. The sample included 5 unilateral, 40 bimodal, and 101 bilateral CI users (77 simultaneously and 24 sequentially implanted). Data Collection and Analysis: Daily CI use, duration, and frequency of coil-offs per day, and the time spent in multiple intensity ranges and environment types were extracted from the datalog saved during clinic appointments. Multiple regression analyses were completed to predict daily CI use based on child-related demographic variables, and to evaluate the effects of age on coil-offs and environment acoustics. Results: Children used their CIs for 9.86 ± 3.43 hr on average on a daily basis, with use exceeding 9 hr per day in ~64% of the children. Daily CI use reduced significantly with increasing durations of coil-off (p = 0.027) and increased significantly with longer CI experience (p < 0.001) and pre-CI acoustic experience (p < 0.001), when controlled for the child's age. Total time in sound (sum of CI and pre-CI experience) was positively correlated with CI use (r = 0.72, p < 0.001). Longer durations of coil-off were associated with higher frequency of coil-offs (p < 0.001). The frequency of coil-offs ranged from 0.99 to 594.10 times per day and decreased significantly with age (p < 0.001). Daily CI use and frequency of coil-offs did not vary significantly across known etiologies. Listening environments of all children typically ranged between 50 and 70 dBA. Children of all ages were exposed to speech in noisy environments. Environment classified as "music" was identified more often in younger children. Conclusions: The majority of children use their CIs consistently, even during the first year of implantation. The frequency of coil-offs is a practical challenge in infants and young children, and demonstrates the need for improved coil retention methods for pediatric use. Longer hearing experience and shorter coil-off time facilitates consistent CI use. Children are listening to speech in noisy environments most often, thereby indicating a need for better access to binaural cues, signal processing, and stimulation strategies to aid listening. Study findings could be useful in parent counseling of young and/or new CI users.